Violinistic resources of the musical tradition of Scissor dance in Huanta, Ayacucho - Valiente Estrada, Karen Giselle (2020)
The scissors dance presents a particular music compared to other musical expressions of the Andean tradition. The interpretation of the violin has acquired its own characteristics that are linked to a range of technical-expressive resources, transmitted through the imitation in the aural tradition, and on which there are not enough studies. In this study, the context of the traditional practice of the violin in Huanta, Ayacucho is approached, recognizing the dynamics of learning the instrument and the role of musical leadership that the violinist assumes. As a central study, the melodic and ornamental resources used during the performance of the violin are analyzed and indicated by musical transcriptions made from a sound source. Parallel to the recognition of these resources, the relationship between their sound embodiment in music and the choreographic expression of the dancer or dansaq is revealed. The results of the research allow us to observe that the execution of the technical-expressive resources on the violin constitutes a substantial aesthetic component in the musical tradition of the Scissors dance.